EVALUATION OF A NATIONAL HOME SAFETY EQUIPMENT SCHEME. (7th October 2012) - Watson, MC; Errington, G; Hamilton, T; Mulvaney, C; Smith, S; Binley, S; Coupland, C; Kendrick, D; Walsh, P
Abstract : Background: The national scheme was established in England in 2009 with £18m, running for 2 years. It targeted families with children under 5 living in areas with the highest accident rates in England. Scheme components included: training for professionals; home safety checks; advice for families; free provision and installation of home safety equipment. The Royal Society for the Prevention of Accidents established and managed the scheme nationally. Delivery was through a range of local organisations. Independent evaluation was conducted by the University of Nottingham. Aims/Objectives/Purpose: To evaluate the national scheme; specifically investigating effectiveness, appropriateness and reach. Methods: This complex evaluation employed multiple methods including postal surveys, one-to-one interviews, direct observation, case studies, documentary analysis and postcode mapping of family data. Results/Outcome: The evidence gathered from a range of sources and perspectives was very positive with regard to the implementation and value of the scheme. A total of 129 local schemes were active covering 92% of the original target areas. Safety equipment was professionally fitted in 66 127 homes and 282 000 families had received home safety information. Mapping the postcodes for families in receipt of equipment confirmed that 70% resided in the most deprived areas of England. The distribution of supporting resources included 7881 DVDs, 3885 flipcharts and 568 000 height charts. Feedback from families and professionals was positive. Significance/Contribution to the field: The evaluation has implications both for future home safety equipment schemes and the evaluation of large injury prevention interventions.